PENGARUH METODE DISKUSI KELAS TERHADAP KETERAMPILAN BERKOMUNIKASI MAHASISWA FAKULTAS DAKWAH DAN KOMUNIKASI UNISNU JEPARA - Mahfudlah Fajrie; Childa Fauzia (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2021)
This study aims to determine the effect of the class discussion method on the communication skills of students of the Faculty of Da'wah and Communication at UNISNU Jepara. The hypothesis proposed in this study is that there is an effect of the class discussion method on the communication skills of students of the Da'wah and Communication Faculty, especially in the Islamic Communication and Broadcasting study program. The subjects in this study were all active students from the 2017-2020 class. The total number of students is 92 people consisting of 40 males and 52 females. The sampling technique used is non-probability sampling with saturated sampling type. Data collection methods consist of observation, interviews and questionnaires. The data were analyzed using the IMB SPSS Statistics 25 application. The results of the correlation test using the product moment correlation analysis between the discussion method and communication skills were 0.634 with a significant product moment correlation coefficient of 0.000. With a value of 0.634, it is close to a value of 1. which means that there is a significant and positive influence between the variable discussion method-communication skills on the variable communication skills-discussion method.